On the identity of Cacopsylla nasuta (Horváth, 1904) (Hemiptera: Psyllidae) - Lashkari, Mohammadreza; Burckhardt, Daniel; Manzari, Shahab (Zootaxa, 2022)
Cacopsylla nasuta (Horváth), which is newly recorded from Iran, is redescribed based on specimens collected on Hippophae rhamnoides. The species is morphologically similar to but distinct from Cacopsylla hippophaes (Foerster). Morphological characters are discussed for separating the two taxa. It is concluded that C. nasuta is restricted to the mountain ranges of Iran, Central Asia, Siberia and probably the Caucasus, and C. hippophaes to Europe. Probably all previous records of C. hippophaes from Asia concern C. nasuta. Specimens from Afghanistan and Turkey, provisionally referred to C. nasuta, are not conspecific with specimens from Iran.